Konsep diri perempuan pengemudi truk trailer - Al Kamil, Moh. Arvani Zakky; Selmi, Sebtiani (Journal of Indonesian Psychological Science (JIPS), 2022)
ABSTRACTWomen in male-dominated jobs such as truck drivers are rare. However, the presence of women who work as truck drivers shows the toughness of women who are often underestimated in terms of gender equality. the purpose of this study was to describe the role of women as trailer truck drivers and to find out the characteristics and self-concept of women freight drivers in Malang Regency. This study uses a qualitative method with a phenomenology approach. Data collection techniques used are through observation, in-depth interviews, and documentation. The data analysis technique used in this research is descriptive qualitative analysis. While testing the validity of the data was done by triangulation of sources. The results of this study indicate that women have a positive self-concept in carrying out hard work that is rarely of interest to women in general. The implication is that women can undergo various fields of work by strengthening their self-concept.KEYWORDS:  self concept; woman truck driver; self image ABSTRAKPerempuan dalam pekerjaan yang didominasi laki-laki seperti pengemudi truk jarang dijumpai. Namun adanya perempuan yang berprofesi sepagai supir truk menunjukkan ketangguhan perempuan yang seringkali diremehkan dalam kesetaraan gender. Tujuan penelitian ini adalah untuk mendeskripsikan peran wanita menjadi pengemudi angkutan barang dan untuk mengetahui karakteristik dan konsep diri wanita pengemudi angkutan barang di Kabupaten Malang. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Pengumpulan data teknik yang digunakan adalah melalui observasi, wawancara mendalam, dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif. Sedangkan uji keabsahan data dilakukan dengan triangulasi sumber Hasil penelitian ini menunjukkan bahwa perempuan memiliki konsep diri positif dalam menjalani pekerjaan berat yang jarang diminati oleh perempuan pada umumnya. Implikasinya perempuan dapat menjalani berbagai bidang pekerjaan dengan memperkuat konsep dirinya. KATA KUNCI Konsep diri; perempuan truk trailer; gambaran diri Copyright ©2022. The Authors. Published by Journal of Indonesian Psyhological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0